Adsorption Isotherms For Phenol Onto Activated Carbon. - Maarof, Hawaiah Imam; Hameed, Bassim H.; Ahmad, Abdul Latif (De La Salle University Press Inc, 2004)
This laboratory study investigated the effectiveness of two types of activated carbons (ACs), NORIT Granular Activated Carbon (NAC 1240) and NORIT Granular Activated Carbon D10 (NAC D10),for the removal of phenol from aqueous solutions. The study was carried out under batch mode at different initial concentrations (10-60mg/I) and at temperature of 30°C. The adsorption isotherm parameters for the Langmuir and Freundlich models were determined using the adsorption data. It was found that both the Langmuir and the Freundlich isotherms described well the adsorption behavior of phenol on NAC D10, while the Freundlich isotherm described very well the adsorption of phenol on NAC 1240.